Oleuropein alleviates malathion-induced oxidative stress and DNA damage in rats. Issue 1 (2nd January 2016) - Karabag-Coban, Funda; Bulduk, Ibrahim; Liman, Recep; Ince, Sinan; Cigerci, Ibrahim; Hazman, Omer
Abstract : The effects of acute exposure to 250 mg/kg malathion and the protective effects of 20 mg/kg oleuropein, both administered intraperitoneally, were evaluated in Wistar male rats. Malathion administration increased malondialdehyde, nitric oxide, 8-hydroxy-2′-deoxyguanosine, total oxidant status, and DNA damage, yet decreased total antioxidant activity, superoxide dismutase, and catalase activities in blood, liver, and kidney. Administration of oleuropein reversed malathion-induced oxidative stress, lipid peroxidation, DNA damage, and antioxidant enzyme activity.